Un metodo alternativo en el tipo de poda al plantar chopos en regadio - Hernandez Leon, M.=700 1 Padro, A.
(En, Es)
Ilus., 6 ref.
Keywords: POPULUS; PODA; PLANTACION; REGADIO; METODOS; ESPAÑA; CHOPO; ANALES DEL I.N.I.A.